Financial Stability and Interest-Rate Policy : A Quantitative Assessment of Costs and Benefits - Pescatori, Andrea (IMF Working Papers; Working Paper ;, 2016)
Should monetary policy use its short-term policy rate to stabilize the growth in household credit and housing prices with the aim of promoting financial stability? We ask this question for the case of Canada. We find that to a first approximation, the answer is no- especially when the economy is slowing down.